Behaviour of Corrugated Composite Tube Under Compressive Load Using Finite Element Method - Ng, Seet Wai (2009)
This work focuses on studying the effect of composite corrugated tubes’ crushing behaviour and to identify the optimised energy-absorption orientation of composite material lamination subjected to the axially compressive load. Parametric study was conducted to investigate the effect of the corrugated angles and fibre orientations on the energy absorb using the E-Glass fibre/epoxy Corrugated Cylindrical Composite Tubes (CCCT) in woven roving form. Twenty different orientations ([0/0/0], [30/0/0], [0/45/0], [60/0/0], [30/0/30], [30/45/0], [60/0/30], [45/0/45], [60/45/0], [60/0/60], [30/30/30], [30/45/30], [60/30/30], [30/45/45], [60/45/30], [30/60/60], [45/45/45], [60/45/45], [60/45/60], [60/60/60]) of E-Glass fibre/epoxy in woven roving laminations were fabricated for this purpose. Nevertheless, only three randomly chosen corrugated angles (5 degrees, 20 degrees & 35 degrees) were used for finite element analysis. Typical failure histories of their failure mechanisms are presented and discussed. Results showed that the crushing behaviour and the energy-absorption level of composite corrugated tube are found to be different when changes are made to the orientation of lamination of the composite material. CCCTs with the lowest corrugation angles resulted with highest initial crushing load and the highest average crushing load, and vice-versa. Meanwhile, CCCTs with the low corrugated angle requires thorough study before being used as an energy absorption device because their initial crush load that is too much greater than the average crush load itself. However, the best energy absorbing CCCT for this work should have the highest possible energy absorbed per unit mass (Es) while compensating for least possible differences between initial crush load and average crush load. With this criterion, CCCT with a corrugated angle of 20 degrees and [60/0/60] lamination orientation fulfilled the requirement. At the same time, the result of this work also shows that the average Es for CCCT with a lower corrugated angle is higher than the CCCT with a higher corrugated angle. Subsequently, the usage of 5, 20 and 35 degrees corrugated angles has generally covered the range of corrugated angles from 0 degree to 45 degrees because as the corrugated angle of CCCTs increases, the average Es of CCCT will reduce and will no longer significant in this project. CCCT with a corrugated angle of beyond 45 degrees will cause the woven roving composite material of CCCT to perform beyond the intended strength of direction. In addition, corrugated angles between 45 degrees and 90 degrees are similar to corrugated angles from 0 degree to 45 degrees. Thus, no study on CCCTs with corrugated angle beyond 45 degrees is required.